Applicability of single-step genomic evaluation with a random regression model for reproductive traits in turkeys (Meleagris gallopavo) - Makanjuola, Bayode O.; Abdalla, Emhimad A.; Wood, Benjamin J.; Baes, Christine F. (Frontiers in Genetics, 2022)
Fertility and hatchability are economically important traits due to their effect on poult output coming from the turkey hatchery. Traditionally, these traits are collected throughout the productive life of the bird and are cumulated, resulting in each bird having a single record per trait. Genetic evaluations of these traits have been estimated using pedigree relationships. However, the longitudinal nature of the traits and the availability of genomic information has renewed interest in using random regression (RR) to capture the differences in repeatedly recorded traits, as well as the incorporation of genomic relationships. Therefore, the objectives of this study were to compare the applicability of a RR model with a cumulative model (CUM) using both pedigree and genomic information for genetic evaluation of FERT, HOF and HOS, and estimate selection response from the models. For this study, a total of 63,935 biweekly FERT, HOF and HOS records from 7,211 hens mated to 1,524 toms were available for a maternal turkey line. In total, 4,832 animals had genotypic records and pedigree information on 11,191 animals was available. Estimated heritability from the CUM model using pedigree information was 0.11  0.02, 0.24  0.02 and 0.24  0.02 for FERT, HOF, and HOS, respectively. With random regression using pedigree relationships, heritability estimates ranged from 0.04-0.09, 0.11-0.17 and 0.09-0.18 for FERT, HOF, and HOS, respectively. The incorporation of genomic information increased heritability by an average of 28% and 23% for the CUM and RR models, respectively. In addition, the incorporation of genomic information caused accuracy to increase by approximately 11% and 7% for HOF and HOS, respectively, however, a decrease in accuracy of about 12% was observed for FERT. Expected selection responses ranged from 1.06 to 5.88% in trait units per year for all studied traits. Selection responses estimated from RR increased more than two-fold compared to the CUM model. Likewise, selection responses estimated using only pedigree information were lower than those that included genomic information. Our findings suggest that RR models using pedigree and genomic relationships will achieve a higher response to selection in comparison to the traditional CUM model.